Integrating a Character-Based Curriculum to Build Children's Resilience Against Violence and Negative Digital Impacts - Yossi Srianita; Azi Matur Rahmi; Gina Asri Ruwaida; Dwiyani Anggraeni (Suluah Pasaman, 2026)
The development of digital technology presents both opportunities and challenges for early childhood. Increased use of devices without adequate guidance has the potential to lead to digital addiction, exposure to age-inappropriate content, cyberbullying, and impaired social-emotional development. This study aims to analyze the application of character education and patterns of digital media use in early childhood, formulate a curriculum integration model based on character education and healthy digital habits, and examine its implementation in building children's resilience against the negative impacts of digital media. The study used a qualitative descriptive approach with observation, interview, and documentation techniques. Informants consisted of early childhood education teachers, parents, and children aged 4–6 years in Cikedokan Village, Bekasi Regency. Data were analyzed through data reduction, data presentation, and drawing conclusions using triangulation of sources and techniques. The results show that character education has been implemented in learning, but has not been systematically integrated with digital literacy. Children exhibited quite high intensity of device use with limited guidance. The developed integration model combines the values ​​of discipline, responsibility, and empathy through screen time management, media use guidance, and healthy digital behavior habits. Implementation of the model contributed to improving children's ability to control device use and adapt to digital risks. These findings suggest that integrating character education and digital literacy into the early childhood education curriculum can strengthen children's resilience in the digital age